Tunable Diode-Laser Absorption Spectroscopy for Trace-Gas Measurements with High Sensitivity and Low Drift - Dyroff, Christoph (Karlsruhe Series in Photonics & Communications / Universität Karlsruhe (TH), Institute of High-Frequency and Quantum Electronics (IHQ), 2009)
This book discusses the mechanical and opto-electronic design of laser spectrometers for measuring two very important atmospheric gases, namely water vapor and its isotopic ratios, and formaldehyde. For measuring water vapor, shot-noise limited sensitivity has been achieved by a careful choice of system components and data processing. For measuring formaldehyde, a selective sample modulation exploiting the Stark effect has been used to greatly improve the sensitivity.